(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
This paper was conceived in the research developed by the author for the elaboration of his doctoral thesis, and aims to promote a reflection on the article that the playwright Jorge Andrade published in Revista Anhembi nº 87 of February 1958, where he describes the excellence of Cacilda Becker’s work, mainly in the production of Poil de Carotte, a show watched by him in 1950, placing the actress on the level of the genius of the theater’s, Sacred monster.